A critique of the use of psychometric assessments with visually impaired children and young people. Issue 2 (2nd April 2020) - Minks, Adrian; Williams, Huw; Basille, Karen
ABSTRACT: For 40 years there has been a call for improvement in assessing the academic potential of children and young people (CYP) with visual impairment. Anecdotal evidence regarding the use of psychometric assessments with CYP with visual impairment suggests that some professional practice has involved the use of assessments normed on a sighted population. Moreover, often only the verbal components have been administered. However, such a narrow approach can lead to a skewed cognitive profile. This paper discusses the validity for the continued use of psychometric assessments that are not wholly appropriate for use. Furthermore, popular psychometric assessments are investigated regarding their potential for useful and appropriate adaptation. In many instances, reasonable adjustments could make these tests more accessible, thereby offering a more equitable process, although significant questions continue to exist about the vexed issue of using psychometric assessments with the wider population of CYP, let alone this distinct group.